Defunding controversial industries: Can targeted credit rationing choke firms? - Sachdeva, Kunal; Silva, André F.; Slutzky, Pablo; Xu, Billy Y. (Journal of Financial Economics, 2025)
This paper examines the effects of targeted credit rationing by banks on firms likely to generate negative externalities. We exploit an initiative of the U.S. Department of Justice, labeled Operation Choke Point, which compelled banks to limit relationships with firms in controversial industries. Using supervisory loan-level data, we show that, as intended, targeted banks reduced lending and terminated relationships with affected firms. However, most of these firms fully substituted credit through nontargeted banks under similar terms. Overall, we find no significant shifts in the performance and investment of affected firms, suggesting that targeted credit rationing is widely ineffective in promoting change.